Assessing the Imagination Scale’s Nomological Validity: Effect of Hedonic versus Utilitarian Product Types and Abstract versus Concrete Advertising Execution - Ike Janita Dewi; Swee Hoon Ang (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
This research builds on a study of advertisement-evoked imagination scale developed by Dewi and Ang (2015). The imagination scale contains four types of imagination, that is, benefit-anticipatory imagination, emotional-bonding imagination, symbolic imagination, and mind-wandering imagination.In this paper, the proposed constructs of the imagination types are related to other relevant constructs existing in marketing literature.The purpose of this research is twofold. First, it establishes the nomological validity of the imagination measures by placing it in the context of hedonic-utilitarian concepts proposed by Holbrook and Hirschman (1983). Second, the research empirically studies the effect of situational factor, that is concrete versus abstract advertisement execution, on imagination elicitation. The study is an experiment which employs mixed factor design involving eight sub-groups of participants. Results of the research demonstrate the nomological validity of the imagination scale where the four types of imagination were elicited in response to hedonic/utilitarian product depicted in the ad and situational factors (that is, abstract versus concrete ads).